Recommendations for improving Quality of Research in Medical Institutes - Mughal, Arsalan Manzoor (Journal of University College of Medicine and Dentistry, 2022)
Research output from Pakistan is gradually increasing. The “Pakistan Research and Innovation Landscape Report” states that research output from Pakistan has increased three hundred times in the Web of Science Core Collection. Among the disciplines, the largest number was from Clinical Medicine and its Normalized Impact is greater than the World average. This achievement is due to a large number of medical colleges in the country. Pakistan currently has 114 medical colleges which are the fifth largest in the world after India, Brazil, China, and the United States of America.